Leveraging Climate Finance through Green Bonds for Sustainable Transport Development in Nigeria - Enaikpobomene Mina Irejeh; Ekiyeghazi Samuel Oyakegha; Sile Alex Akpoboloemi (My University, 2025)
Climate change poses a critical threat to sustainable development, particularly in developing economies such as Nigeria where infrastructure deficits are compounded by environmental vulnerabilities. This study investigates leveraging climate finance through green bonds in for sustainable transport development in Nigeria. The purpose of the study is to consider how green bonds can be mobilized to finance sustainable transport development in Nigeria. The study adopted qualitative research technique by sytnhetisizing both theoretical and empirical literature. Based on literature synthesis the study revealed that although Nigeria has taken commendable steps, such as issuing sovereign green bonds, the transport sector remains largely excluded from green bond financing. The study identifies key constraints including weak institutional capacity, limited investor awareness, absence of sector-specific green bond guidelines, and insufficient policy incentives. However, it also highlights significant opportunities for aligning Nigeria’s transport development with its climate commitments under the Paris Agreement and Nationally Determined Contributions (NDCs). The research contributes to knowledge by offering a sector-specific analysis of green bond deployment. It is therefore recommended that targeted policies such as tax incentives, public-private partnerships (PPPs), and capacity-building initiatives. It concludes that with appropriate regulatory frameworks and stakeholder engagement, green bonds can become a transformative tool for financing sustainable transport infrastructure in Nigeria.
Keywords: Climate finance; Climate resilience; Green bonds; Policy instruments; Public-private partnerships; Sustainable transport Infrastructure; Nigeria